Aplicación de NIIF para Pymes e incidencia en la información financiera de las Pequeñas Empresas Manufactureras del Régimen General en la ciudad de Tarapoto. Año 2013 - Palacios Huamán, Jhon Hitler (2014)
In the present investigation, we started analyzing the situation in the application of IFRS in most companies in our country and in our region, especially we focus on SMEs, since these are the most important driver in national economy. Furthermore, the content of the research the text of the IFRS for SMEs and the Law amending some articles of the MSEs Act mentioned, information gathered from previous theses related to the subject cited, discussed didactically sections containing the IFRS for SMEs and the importance of its application in manufacturing companies in the city of Tarapoto. Information related to the input offered by SMEs and manufacturing enterprises, the development of the San Martin region was collected. The analysis and application of the rule allowed to conclude that the financial statements under international financial reporting standards show high quality information and above all reasonably reflect the financial position and performance that has been a feature in certain period.